2022
DOI: 10.3390/ph15040487
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Anti-Bacteria by Carbon Dots and Their Nano-Composites

Abstract: The misuse of many types of broad-spectrum antibiotics leads to increased antimicrobial resistance. As a result, the development of a novel antibacterial agent is essential. Photodynamic antimicrobial chemotherapy (PACT) is becoming more popular due to its advantages in eliminating drug-resistant strains and providing broad-spectrum antibacterial resistance. Carbon dots (CDs), zero-dimensional nanomaterials with diameters smaller than 10 nm, offer a green and cost-effective alternative to PACT photosensitizers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 121 publications
0
22
0
Order By: Relevance
“…These passivated sites promote bactericidal functions owing to the creation of redox species and emissive excited states; the dots directly transfer energy to molecular oxygen, generating 1 O 2 . Worth noting that the antibacterial response also depends on the CDs concentration, the dose, and the time of irradiation (F. Cui et al, 2020; Dong et al, 2017; Su et al, 2022; Wu, Abbas, Yang, Li, Tedesco, & Bi, 2022).…”
Section: Cds For Bacteria Eliminationmentioning
confidence: 99%
“…These passivated sites promote bactericidal functions owing to the creation of redox species and emissive excited states; the dots directly transfer energy to molecular oxygen, generating 1 O 2 . Worth noting that the antibacterial response also depends on the CDs concentration, the dose, and the time of irradiation (F. Cui et al, 2020; Dong et al, 2017; Su et al, 2022; Wu, Abbas, Yang, Li, Tedesco, & Bi, 2022).…”
Section: Cds For Bacteria Eliminationmentioning
confidence: 99%
“…The photothermal therapy (PTT) effect induced by NIR laser irradiation to increase local temperature was also a mechanism leading to bacterial death, such as metal CDs‐based composites. [ 212,216 ] For instance, a curcumin loaded CD composites with synergistic PDT and PTT antibacterial effects under dual wavelength illumination was constructed to improve the damage extent of the bacterial cell membrane and achieve efficient antibacterial treatment (Figure 6d). [ 213 ] In another work, the surface of CDs was functionalized with bovine serum albumin (BSA) (BSA‐CDs), which drastically altered its fluorescence emission wavelength and increased the production of ROS (Figure 6e).…”
Section: Cds‐based Composites With Different Physicochemical Propertiesmentioning
confidence: 99%
“…178 Nie et al and Xu et al have demonstrated that selenium-doped carbon dots specifically attach to RNA, which results in the generation of ROS that harms the nuclear membrane. 179,180 Additionally, CDs were proven to be efficient for concurrent improved fluorescence imaging and PDT of gastric malignancy in vivo . 181 Because of their low cytotoxicity, CDs can be conjugated with conventional photosensitizers (PS) to increase the organic PS water dispersibility.…”
Section: Advantages Of Red Carbon Dotsmentioning
confidence: 99%